Exogenous Abscisic Acid Confers Salinity Tolerance in Chlamydomonas reinhardtii During Its Life Cycle. Issue 4 (15th May 2021) - Abu‐Ghosh, Said; Iluz, David; Dubinsky, Zvy; Miller, Gad
Abstract : The plant hormone abscisic acid (ABA) coordinates responses to environmental signals with developmental changes and is important for stress resilience and crop yield. However, fundamental questions remain about how this phytohormone affects microalgal growth and stress regulation throughout the different stages of their life cycle. In this study, the effects of ABA on the physiology of the freshwater microalga Chlamydomonas reinhardtii at its different life cycle stages were investigated. Exogenously added ABA enhanced the growth and photosynthesis of C. reinhardtii during the vegetative stage. The hormone also increased the tolerance of this alga to high‐salinity stress during gamete formation under nutrient depletion, as well as it extended their survival. We show that the level of reactive oxygen species (ROS) generated in the ABA‐treated cells was significantly less than that in the untreated cells under inhibiting NaCl concentrations. Cell size examination showed that ABA prevents cells from forming palmella when exposed to high salinity. All together, these results suggest that ABA can support the vitality and survival of C. reinhardtii under high salt conditions.